Adjuvant Anticholinesterase Therapy for the Management of Epilepsy‐Induced Memory Deficit: A Critical Pre‐clinical Study. (1st July 2014) - Mishra, Awanish; Goel, Rajesh Kumar
Abstract Epilepsy is one of the major neurological disorders still awaiting safer drugs with improved antiepileptic effect and lesser side effects. Apart from epilepsy itself, AEDs also have been shown to induce cognitive impairment in patients with epilepsy. There are limited data for the treatment of this menace. As cholinergic approach has widely been practiced for the restoration of memory in various neurodegenerative disorders, this study was envisaged to evaluate add on effect of acetylcholinesterase inhibitor (tacrine) with phenytoin in pentylenetetrazole‐kindling‐induced learning and memory deficit in mice. In this study, mice were kindled using subconvulsive dose of pentylenetetrazole (35 mg/kg, i.p.; at interval of 48 ± 2 hr) and successfully kindled animals were divided into different groups and treated with vehicle, phenytoin and phenytoinin in combination with tacrine (0.3 mg/kg), atropine (1 mg/kg) and tacrine + atropine. Effect of different interventions on learning and memory was evaluated using elevated plus maze and passive shock avoidance on days 5, 10, 15 and 20. Phenytoin‐treated kindled animals were associated with learning and memory deficit, while tacrine supplementation improved memory deficit with increased seizure severity score. Atropine treatment significantly reversed the protective effect of tacrine. Neurochemical findings also support the behavioural finding of the study. Our results suggest the use of anticholinesterases, with better seizure tolerance, for the management of cognitive impairment of epilepsy, as adjunct therapy.